1988
DOI: 10.1016/0014-5793(88)81044-5
|View full text |Cite
|
Sign up to set email alerts
|

A case of carnitine palmitoyltransferase II deficiency in human skeletal muscle

Abstract: A 20-year-old man was shown to have a deficiency of carnitine palmitoyltransferase (CPT) II in skeletal muscle. The evidence was: (i) there was no significant oxidation of [9,10 -3 H]palmitate or of[1-14C]palmitate in mitochondrial fractions from fresh skeletal muscle from the patient; (ii) all the CPT activity in a homogenate of fresh muscle from the patient was overt (CPT I) with no increase in activity after the inner membrane was disrupted; (iii) all the CPT activity in the patient's muscle was inhibited b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 27 publications
(27 reference statements)
1
8
0
Order By: Relevance
“…However, the fact remains that total CPT activity was normal when measured under optimal assay condition using either the isotope exchange assay or the isotope forward assay. This has also been demonstrated in several other studies [7,17,21,23,25,26,29,34].…”
Section: Defect Of Cpt H In Cpt Deficiencysupporting
confidence: 65%
See 1 more Smart Citation
“…However, the fact remains that total CPT activity was normal when measured under optimal assay condition using either the isotope exchange assay or the isotope forward assay. This has also been demonstrated in several other studies [7,17,21,23,25,26,29,34].…”
Section: Defect Of Cpt H In Cpt Deficiencysupporting
confidence: 65%
“…Biochemical and recent molecular evidence suggests that CPT II is affected in muscular CPT deficiency [24,[26][27][28]. Several biochemical studies, however, have indicated that total CPT activity measured under optimal assay conditions is normal in these patients but is abnormally inhibited by malonyl-coenzyme A (malonyl-CoA), Triton X-100, palmitoyl-CoA, and palmitoylcarnitine [7,17,21,23,25,26,29,34]. Therefore it has been suggested that CPT deficiency is not due to persistent loss of total CPT, CPT I, or CPT II activity but is caused by an abnormally regulated CPT [34].…”
mentioning
confidence: 99%
“…It was confirmed subsequently by direct enzyme measurement in fibroblast homogenates that the first patient had a deficiency of the long-chain 3-hydroxyacyl-CoA dehydrogenase component of the trifunctional enzyme (patient: 10.6 nmol NADH reduced per minute per milligram of protein; mean t SD for six controls: 36.9 + 6.8 nmol NADH reduced per minute per milligram of protein). The CPT-I1 deficiency was proven in the second patient by measurement of CPT activity in fibroblasts using the radiochemical forward assay (13).…”
Section: Methodsmentioning
confidence: 99%
“…However, after preincubation of the muscle homogenate of CPT II muscle deficiency patients with trypsin, the total CPT activity slightly increased and rendered the activity greatly insensitive to inhibition by malonyl-CoA in both patients and controls [ 20 ]. In one Western blot study on one patient, there was no detectable CPT II protein at all [ 21 ]. In another immunoreactivity study, prior to the identification of the disease-causing mutations, five groups of patients were differentiated according to enzyme activity and protein content, but none of the patients had complete loss of the CPT protein [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another immunoreactivity study, prior to the identification of the disease-causing mutations, five groups of patients were differentiated according to enzyme activity and protein content, but none of the patients had complete loss of the CPT protein [ 16 ]. However, in these studies, antibodies against bovine liver CPT II [ 21 ] and rat liver CPT II [ 16 ] have been used. The p.S113L mutation represents a missense mutation, and does not lead to a truncated protein [ 22 ].…”
Section: Introductionmentioning
confidence: 99%